Use of Process Simulation for Plant Debottlenecking - Zulfan Adi Putra (Universitas Pendidikan Indonesia, 2016)
This paper was aimed to illustrate the use of process simulation tools to find bottlenecks in a chemical plant. In practice, finding the first bottleneck of a plant is simply by increasing the capacity. However, two questions remain, e.g. what would the next bottleneck be and how big the first bottleneck needs to be expanded until the next bottleneck is reached. These questions can be repeated until eventually the whole equipment in the plant needs to be debottlenecked. Since it is impossible to answer the above questions in practice, a process simulation approach is utilized. Relevant equipment data and a validated thermodynamic model are used to build such a model. Plant performance trials are taken into account to estimate practical parameters such as fouling coefficients and plate tightness. This work requires strong interactions between operational people, consistent data gathering, and process simulation skill. The approach used in this work has shown that a reasonably accurate model can be built. The result has shown that the model can identify the first bottleneck as confirmed on the field. Sequence of bottlenecks and their corresponding increment of capacity increase have also been identified. The simulation results also illustrate the use of process simulation for plant debottlenecking.